Recurrent cardiovascular events in patients with type 2 diabetes and haemodialysis: analysis from the 4D Study - Marx, Nikolaus; Wanner, Christoph; Jankowski, Joachim; März, Winfried; Krane, Vera; Genser, Bernd (Clinical kidney journal, 2023)
In the ‘Die Deutsche Diabetes Dialyse Studie’ (4D Study), treatment of patients with type 2 diabetes mellitus (T2DM) on haemodialysis (HD) with atorvastatin compared with placebo had no significant effect on the first composite primary major adverse cardiovascular event (MACE) endpoint of death from cardiac causes, fatal stroke, non-fatal myocardial infarction or non-fatal stroke. In this study we analysed first and recurrent events in 1255 patients from the 4D Study.We conducted an event history analysis to investigate the effects of previous clinical events on the risk of different endpoints in the total patient group and after stratification by randomization group.During a median follow-up of 4 years, a total of 548 MACEs occurred, with 469 first and 79 recurrent events. The most frequent event was sudden cardiac death, followed by death due to infection/sepsis. Of the 548 total MACEs, 260 occurred in the atorvastatin group and 288 in the placebo group [hazard ratio 0.91 (95% confidence interval 0.76-1.07), P = .266]. Interestingly, analyses of the baseline hazard functions for first and recurrent events as a function of time after randomization demonstrated that the risks of the composite primary endpoint continually increased in the placebo group with increasing time in the study, whereas the risk in the atorvastatin group remained constant after ≈1.5 years.This recurrent and total event analysis from the 4D Study underscores the high risk of sudden cardiac death and death due to infection/sepsis in patients with T2DM receiving HD and raises the hypothesis that atorvastatin may stabilize cardiovascular risk only after 1-2 years in this high-risk population.We analysed first and recurrent events in 1255 patients with type 2 diabetes mellitus (T2DM) on haemodialysis (HD) from the `Die Deutsche Diabetes Dialyse Studie', in which treatment with atorvastatin compared with placebo had no significant effect on the first composite primary major adverse cardiovascular event. Our data suggest that sudden cardiac death and death caused by infection/sepsis were the most frequent events in patients with T2DM receiving HD. In addition, our analysis on baseline hazard functions for first and recurrent primary endpoint events raises the hypothesis that atorvastatin may stabilize cardiovascular risk in this population after 1.5 years.
Online veröffentlicht: 2. März 2023
Gesehen am 06.08.2024